Statistical process control for managers - Sower, Victor E. (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2014)
Davis Balestracci recently wrote, "When I look at training materials or books (on statistical process control), their tendency is to bog down heavily in the mechanics of construction without offering a clue about interpretation." If you have been frustrated by very technical statistical process control (SPC) training materials, then this is the book for you. This book focuses on how SPC works and why managers should consider using it in their operations rather than on how to calculate limits for control charts. It provides the reader with a conceptual understanding of SPC so that appropriate decisions can be made about the benefits of incorporating SPC into the process management and quality improvement processes. An extensive list of references is provided for those readers who wish to dig deeper into the technical details of SPC. SPC is designed to facilitate making better, more informed decisions about processes. SPC can indicate whether a process should be adjusted or left alone. It can also indicate when a process needs improvement to meet requirements, often can indicate a starting point for improvement projects, and can also provide documentation of the results of process improvement activities.
1. The value SPC can add to quality, operations, supply chain management, and continuous improvement programs -- 2. Variation and what it means to be in control and capable -- 3. Introduction to control charts -- 4. Basic control charts for variables -- 5. Advanced control charts for variables -- 6. Control charts for attributes -- 7. Process capability -- 8. SPC in service industries -- Appendix A. Bare bones introduction to basic statistical concepts -- Appendix B. SPC software used to illustrate this book -- Notes -- References -- Index.
Part of: 2014 digital library.
Includes bibliographical references (pages 135-137) and index.
Title from PDF title page (viewed on August 21, 2014).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Process control -- Statistical methods; variation; statistical process control; SPC; process capability; SPC use; SPC implementation; out of control; control chart; Electronic books